The influence of brand image, product quality, and promotion on customer satisfaction with purchase decisions as intervening variables - Tria Aulia Rosty; Hermiyetti Hermiyetti (Sean Institute, 2024)
This study aims to investigate the impact of brand image, product quality, and promotion on customer satisfaction, considering purchase decision as an intervening variable. The research focuses on iPhone smartphone users at the Faculty of Law, Sultan Agung University. The research method employed is quantitative descriptive analysis with 300 active students as the sample, where data were collected through online questionnaire distribution using Google Form. The results of hypothesis testing indicate that brand image, product quality, promotion, and purchase decision collectively have a significant positive impact on customer satisfaction. Although not all factors reach the expected level of statistical significance, this finding emphasizes the importance of considering the interaction among these factors in designing effective marketing strategies. Managerial implications include maintaining a positive brand image, improving product quality, optimizing promotional strategies, and enhancing consumer purchasing experience. Theoretical implications involve contributing to understanding the relationship among brand image, product quality, promotion, purchase decision, and customer satisfaction, as well as highlighting the complexity of promotional influence in the context of purchase decisions. The limitation of this study lies in the use of a limited sample from one faculty at one university, necessitating cautious generalization of the findings.